Antimicrobial susceptibility of anaerobic organisms isolated from clinical specimens at Charlotte Maxeke Johannesburg Academic Hospital - Naidoo, Sudeshni (My University, 2010)
Anaerobic bacteria cause serious life-threatening infections such as endocarditis, sepsis, intra abdominal, pleuro-pulmonary and central nervous systems infections. Most infections are polymicrobial and involve aerobes and anaerobes. Empiric therapy is generally based on the expected pathogens and the particular type of infection. Even when specimens are cultured and anaerobes identified, not all laboratories perform susceptibility testing. The clinician often relies on published surveillance data when selecting treatment regimens. Antimicrobial susceptibility of anaerobic bacteria is becoming increasingly unpredictable. Resistance can vary significantly and patterns differ geographically, and even within units of the same hospital. From June 2005 until February 2007, 180 consecutive anaerobes isolated from relevant, non- repetitive clinical specimens were tested routinely with the E test method for susceptibility to amoxicillin/ clavulanate (XL), clindamycin (Cm), metronidazole (Mz), penicillin (Pg), ertapenem (Etp), cefoxitin (Fx), ceftriaxone (Tx), chloramphenicol (Cl), and piperacillin/tazobactam (Ptc). The results were read after 48hr incubation in anaerobic conditions. Specimen distribution was as follows: abdominal fluid (3), abscess (7), abdominal abscess (4), aspirates (3), blood cultures (27), bone (3), breast (3), drainage fluid (2), empyema (1), fluids (36), other (4), placental (1), pleural fluid (2), pus (41), tissues (34), umbilicus (1) and unknown sites (8). Bacteroides fragilis was isolated from 81 (45%) clinically significant specimens, followed by Clostridium perfringens 23 (13%), Peptostreptococcus anaerobius 15 (8%) and Prevotella melaniniogenicus 15 (8%). B. fragilis demonstrated a 97.5% resistance to penicillin and 12.3% resistance to metronidazole. C. perfringens exhibited no resistance to penicillin and metronidazole while P. anaerobius had 40% resistance to penicillin and no resistance to metronidazole. P. melaninogenicus was resistant to penicillin in 60% and 6.7% to metronidazole. Overall, chloramphenicol, piperacillin/tazobactam, ertapenem and amoxicillin/clavulanate demonstrated the highest activity to anaerobic isolates, 100%, 99.4%, 97.2% and 96.7%, respectively. Among the 180 tested anaerobes a total of 8.9% resistance has been observed with metronidazole and 81.7% sensitivity with clindamycin. Periodic surveillance to monitor the susceptibility profile of the B. fragilis group and other anaerobic organisms is recommended to create empirical guidelines for appropriate use of antimicrobial agents.
MSc Med, Clinical Microbiology and Infectious Diseases, Faculty of Health Sciences,University of the Witwatersrand, 2009
Keywords: drug resistance; anaerobic bacteria; clinical specimens